Wheat germ as an alternative ingredient to a fair average quality fishmeal in diets for European seabass. (23rd May 2019) - Reis, Bruno; Marques, Alexandra; Campos, Inês; Dias, Ema; Valente, Luisa M. P.
Abstract: Wheat germ (WG) is a by‐product of the flour milling industry and could be a sustainable ingredient to replace a fair average quality fishmeal (FM) in aquafeeds. Subsequently, three diets were tested in European seabass juveniles (IBW: 16.7 ± 2.8 g): control diet without WG (CTRL); two diets with 75 g/kg and 155 g/kg WG (WG8 and WG16, respectively) at the expense of FM. Diets were isoproteic (500 g/kg dry matter, DM) and isoenergetic (21 MJ/kg, DM). After 18 weeks of feeding, apparent digestibility coefficients (ADCs) were determined and growth performance evaluated. Intestine and muscle were collected for histology and fatty acid profile, respectively. Innate immune parameters were evaluated in plasma. DM, protein and phosphorous ADCs increased concomitantly with the inclusion of WG; WG16 reached significantly higher values ( p < 0.05) than CTRL. Feed conversion ratio was lower in fish fed WG16 than in those fed CTRL (1.5 vs. 1.6), while protein efficiency ratio increased with WG inclusion (1.4 vs. 1.2). Results demonstrate WG's potential to partially replace a fair average quality FM in diets for European seabass juveniles without impairing growth and body composition. WG inclusion at 16% (WG16) improved protein ADC and feed utilization, resulting in the lowest economic efficiency ratio, ECR (€/kg fish).